2017
DOI: 10.5664/jcsm.6696
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Sleep Quality, Duration, and Health-Related Quality of Life in Older Chinese: Evidence From a Rural Town in Suzhou, China

Abstract: Study Objectives: To determine the associations of self-reported sleep quality and duration with health-related quality of life (HRQOL) in older Chinese. Methods: We analyzed community-based cross-sectional data of 5,539 individuals aged 60 years and older in the Weitang Geriatric Disease Study. Information of sleep quality and duration were self-reported through participants' responses to predefined questions; HRQOL data were collected by using the European Quality of Life-5 Dimensions (EQ-5D). We estimated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 46 publications
1
28
0
1
Order By: Relevance
“…7 The association between sleep patterns and QOL is strongly influenced by ethnic and sociocultural factors, and therefore it is important to examine their relationship in different sociocultural contexts. 8 Several studies have examined the association between sleep duration and QOL in both general 9,10 and specific populations in China, including schizophrenia, 11 but the findings have been inconsistent. For example, Chiu et al 9 found that short sleep duration was associated with lower QOL, while others 11 did not confirm this finding.…”
Section: Findings Of the Association Between Different Sleep Durationmentioning
confidence: 99%
See 1 more Smart Citation
“…7 The association between sleep patterns and QOL is strongly influenced by ethnic and sociocultural factors, and therefore it is important to examine their relationship in different sociocultural contexts. 8 Several studies have examined the association between sleep duration and QOL in both general 9,10 and specific populations in China, including schizophrenia, 11 but the findings have been inconsistent. For example, Chiu et al 9 found that short sleep duration was associated with lower QOL, while others 11 did not confirm this finding.…”
Section: Findings Of the Association Between Different Sleep Durationmentioning
confidence: 99%
“…Several studies have examined the association between sleep duration and QOL in both general and specific populations in China, including schizophrenia, but the findings have been inconsistent. For example, Chiu et al .…”
Section: Introductionmentioning
confidence: 99%
“…Evidence is emerging that the socio-demographic and lifestyle factors may play a role in sleep disorders among older adults. For instance, female gender, low education, divorce and widowhood, living alone, inadequate fruit intake, drinking tea, alcohol consumption, caffeine, use of certain medications, poor mental health, and physical inactivity have been reported to be associated with sleep disturbance [5,6,[11][12][13][14][15][16][17][18][19][20]. In addition, poor sleep quality or sleep disorders in old people are associated with highly prevalent chronic health conditions, such as hypertension [21], type 2 diabetes [22], cardiovascular disease [23], stroke [24], depression [25], and cognitive impairment [26].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the PSQI score was dichotomized to examine the association between poor sleep quality and anxiety symptoms with good sleep quality as reference group by performing logistic regression models. In the fully adjusted model, we included age, gender , physical activity, marital status, smoking status, drinking status, educational levels, average monthly income and BMI, night sleep duration and napping duration in the model as the underlying confounder according the previous studies [29,30]. Additionally, strati ed analyses were conducted by each potential modi er to examined whether poor sleep quality and anxiety symptoms were potentially changed by age, gender, marital status, smoking status, drinking status, average monthly income , physical activity, BMI, snoring, hypertension, type 2 diabetes mellitus(T2MD).…”
Section: Discussionmentioning
confidence: 99%
“…A web-based study showed that a high prevalence of GAD and poor sleep quality in the Chinese public during COVID-19 outbreak [9]. Some studies have also reported an association between sleep quality and anxiety using PSQI [7,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%